An assessment of the domestication impact on levels of genetic diversity in a synthetic line of giant freshwater prawn (Macrobrachium rosenbergii) for a stock improvement program in Vietnam - Thành, Nguyễn Minh; Mather, Peter (Vietnam Journal of Biotechnology, 2018)
Six microsatellites were used to characterize genetic diversity in three purebred giant freshwater prawn (Macrobrachium rosenbergii) strains that originated from a diallel cross among two wild Vietnamese strain (Dong Nai and Mekong) and a third domesticated Hawaiian strain. All three purebred strains showed relatively high levels of genetic diversity with average number of alleles per locus (A) ranging from 13 to 15. Average observed (Ho) and expected (He) heterozygosities across loci were 0.84 to 0.89 and 0.87 to 0.89, respectively. Microsatellite data from the three purebred strains were pooled together as a basis for estimating the levels of genetic diversity in an synthetic hatchery population and this compared with data for genetic diversity in the three wild populations combined. No significant differences were observed in the relative levels of genetic diversity between the two combined populations. Average A, Ho, and He for the experimental vs. wild reference populations were 24.33 vs. 24.33, 0.87 vs. 0.90, and 0.94 vs. 0.95, respectively. Therefore, an experimental population formed by combining the genetic resources from three purebred strains showed non-significant loss of genetic diversity as a consequence of domestication process. Thus such a synthetic line can provide an important genetically diverse resource for the planned development of GFP culture in Vietnam